Tunable emission of Li4SrCaSi2O4−yN2y/3:Eu2+ phosphors based on anion substitution induction for WLEDs and optical thermometry. Issue 18 (29th April 2022) - Yu, Hua; Zhou, Liuyan; Ye, Renguang; Deng, Degang; Xu, Shiqing
Abstract : Polychromatic emission can be achieved by controlling the distribution of the rare earth activator in multi-cation lattices, which can be used in the fields of white light LED and fluorescence temperature sensing. Abstract : Polychromatic emission can be achieved by controlling the distribution of the rare earth activator in multi-cation lattices, which can be used in the fields of white light LED and fluorescence temperature sensing. However, it is still a challenge to control their distribution and location of the target site in a given host material because the distribution of the rare earth activator is uncertain. In this paper, we have chosen Li4 SrCa(SiO4 )2 as the multi-cation site host and induced the distribution of Eu 2+ ions between different cation sites through anion substitution, for the first time, to regulate the luminescence characteristics of a series of Li4 SrCaSi2 O8− y N2 y /3 :Eu 2+ phosphors. In Li4 SrCa(SiO4 )2 :Eu 2+ phosphors, the substitution of O 2− by N 3− triggered a distinct ordered to disordered structure transition of the SiO4 tetrahedron and induced the remote distribution of the Eu 2+ activator, which was verified through the analysis of the XRD, EPR, FT-IR and fluorescence spectra. Due to the location of Eu 2+ ions in different cation sites (Eu 2+ Sr and Eu 2+ Ca ), two distinguishable emission peaks with tunable color emissions and different responses to temperature were realized. The white LED that utilized blue-orange-emitting Li4 SrCaSi2 O4 N8/3 :Eu 2+ and green-emitting BaSi2 O2 N2 :Eu 2+ (500 nm) displayed an outstanding color rendering index ( R a ) of 85.1. Based on the fluorescence intensity ratio (FIR) technique, an optical temperature measurement mechanism was hypothesized and studied in the temperature range of 293–473 K. The highest S a of the material was 0.086 K −1, and S r was 1.76% K −1 based on the FIR detection technology, revealing obviously better than most inorganic optical temperature-measuring materials reported before. Our work indicates that Li4 SrCaSi2 O8−2 y N4 y /3 :Eu 2+ is a promising material for application in White LEDs and optical thermometers.